Application of Maqasid Syariah in the Act 355 Amendment Proposal (Criminal Jurisdiction): an analysis study / Wan Mohd Amjad Wan Halim, Ahmad Nur Amsyar Zainal and Nur Madihah Zainol Abidin - Wan Halim, Wan Mohd Amjad; Zainal, Ahmad Nur Amsyar; Zainol Abidin, Nur Madihah (Universiti Teknologi MARA, Perlis, 2018)
The discourse about maqasid shariah had been discussed by fiqh scholars since decade. Despite that, the current execution proposal as such the Act 355 Amendment Proposal (Criminal Jurisdiction) is considered as contemporary issue that has caused dilemma amongst the Muslims in Malaysia. This situation said to be rooted from the misinterpretation of both Muslims and non-Muslims community about the implementation of maqasid shariah in the former execution. Thus, this research aims to study about maqasid shariah and its content in the Shariah law application and the implementation of Shariah Law by focusing on the Act 355 Amendment Proposal (Criminal Jurisdiction), Shariah Law Act. Researcher applies qualitative method through library study and data-analysis from different thoughts of fuqaha and Muslim scholars. From the observation, researcher finds that studies about concept of maqasid shariah has been carried out by both classic and contemporary fuqaha, but specific study about maqasid shariah in the Syariah criminal law in Malaysia is still lacking amongst the Muslim scholars.